Genotypic and virulence characteristics of Listeria monocytogenes recovered from food items in Lebanon - Nathaline Haidar-Ahmad; Kohar Annie B Kissoyan; Sukayna M Fadlallah; Rima El-Hajj; Majd Saleh; Nada Ghosn; Ghassan M Matar (Journal of Infection in Developing Countries)
Introduction: Listeria monocytogenes is the agent of listeriosis, a life threatening foodborne disease for immunocompromised patients and pregnant women. This bacterium is not routinely screened for in Lebanon and there is lack of data about the prevalent strains and their potential pathogenicity. To that purpose, this study was undertaken to characterize L. monocytogenes from various food products, by assessing the in vitro biofilm forming ability, detecting their virulence potential, and characterizing them at the strain level. Methodology: Fifty-nine isolates were obtained from the Lebanese Agriculture Research Institute (LARI). They were collected in 2012-2013 from local and imported food products in the Lebanese market. Biofilm formation was measured using the Microtiter Plate Assay. PCR amplification was performed for three main virulence genes; hly, actA, and inlB. Pulsed field gel electrophoresis (PFGE) and BIONUMERICS analysis were carried out. Results: Lebanese isolates from cheese and raw meat showed higher biofilm formation than imported and Lebanese seafood isolates. A total of 100% of the isolates were PCR positive for hly and actA genes and 98.3% for inlB gene. PFGE analysis demonstrated the prevalence of 13 different subtypes with 100% similarity. Detected subtypes were grouped into 6 clusters of 90% genomic similarity. Clustered subtypes were particular to the country of origin. Conclusion: This study highlights the presence of L. monocytogenes in the Lebanese food market with high pathogenic potential and stresses the importance of enhanced surveillance and the implementation of strict regulations on local and imported food. Future investigations may be conducted on a larger food selection.